The effects of therapeutic intermittent hypoxia implementation on complete blood count parameters: an experimental animal model - ŞENGÖR, MUSTAFA; YILDIZ ÖZER, AYSEL; KILIÇ, TALHA (My University, 2022)
Objective: Intermittent hypoxia (IH) implementation is a method performed by intermittently decreasing oxygen concentration in inhaled air at specific rate. This method varies between studies in terms of its application. This study aims to examine the changes in Complete Blood Count (CBC) parameters caused by IH implementation at therapeutic dose ranges with a single model. Methods: Ten Sprague Dawley type adult male rats were divided into two groups. In the study group, FiO2 level of inhaled air, was reduced to 10% in hypoxic cycle. 5 minutes normoxia-hypoxia cycle was used in each 30 minutes experiment period for study group. Control group remained in normoxic air for 30 minutes. 1 cc of blood was taken from mandibular vein from all rats at the end of 6th day. CBC analyzes were performed and differences between two groups were investigated. Results: Significant differences were detected in some CBC parameters between the two groups. It was determined that significant increase in MONO (p<0.001), MONO% (p<0.001), MCH (p=0.03), PLT (p=0.013) and PCT (p=0.007) parameters and significant decrease in MPV (p=0.02) parameters, in favor of study group. Conclusion: IH implementation was caused significant changes in MONO, MONO%, MCH, PCT, PLT and MPV parameters in the CBC analysis of rats. Considering the study results, therapeutic IH implementation may thought to have important effects in terms of lung protection and regeneration. Further research may focus on this point for precising and supporting of this study’ results.
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Intermittent hypoxia; complete blood count tests; animal model